Design of Up-flow Aerated Filters for the Removal of Iron from Groundwater - Thinojah, T.; Ketheesan, B.; Herath, G.B.B. (Water and Development Congress & Exhibition, IWA Proceedings, Colombo, Sri Lanka., 2019)
Groundwater contains iron (Fe) that can be difficult to remove by singular physical-chemical methods. The aim of this presented study was to investigate the suitability of up-flow aerated filters as an upgrading step for the removal of the total Fe from groundwater. Granular activated carbon (GAC) was applied as a pollutant carrier and compared to bio-pac media (BPM) by conducting column test to treat synthetic groundwater (SGW). Initially two adsorption kinetic studies were done for GAC. The effect of influent Fe concentration, hydraulic retention time (HRT) and air supply to the system were investigated using column experiment. The sorption result follows the pseudo-second order kinetics with the adsorption amount of 1.36 mg/g. Column experiment results show that around 99% and 70% Fe removal efficiency can be achieved for the best condition of 3 mg/L influent Fe concentration with 7 hours HRT for GAC and BPM respectively. The air supply into the column did not show any improvement in Fe removal efficiency. The performance of GAC is found to be much better than BPM. All over, the new combined treatment method aeration followed by filtration demonstrated to be an effective technique for Fe removal from groundwater and also satisfied the World Health Organization (WHO) drinking water standard for Fe concentration.
Keywords: Groundwater; Iron removal; Granular activated carbon; Bio pack media; Column test